2008
DOI: 10.1007/s11269-008-9319-8
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-based DRASTIC Model for Assessing Aquifer Vulnerability in Kherran Plain, Khuzestan, Iran

Abstract: The Kherran plain is located in the northeast of Ahwaz in Khuzestan Province, Iran. The state of groundwater pollution is a critical issue with increasing population and agricultural development in Iran. For this reason, vulnerability assessment is an important factor in any policy making decision in any part of country. Focusing on this issue, the article attempts to presents a groundwater vulnerability map for the Kherran plain. The map designed to show areas of highest potential for groundwater pollution ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…The state of groundwater pollution has become critical as the population and agricultural development have increased in Iran. Pollution assessment is an important factor in policymaking in any country [6]. Pollution assessment is a basis for initiating protective measures for important groundwater resources.…”
Section: Introductionmentioning
confidence: 99%
“…The state of groundwater pollution has become critical as the population and agricultural development have increased in Iran. Pollution assessment is an important factor in policymaking in any country [6]. Pollution assessment is a basis for initiating protective measures for important groundwater resources.…”
Section: Introductionmentioning
confidence: 99%
“…Aquifer media is the characteristics of materials by which the aquifer is made of (Chitsazan and Akhtari 2009). For the understanding of the aquifer media, it is necessary to understand the subsurface lithological condition.…”
Section: Aquifer Mediamentioning
confidence: 99%
“…On the basis of the analysis, the entire region was classified into three zones of vulnerabilities and it was found that important cities with higher to medium groundwater vulnerability were located near groundwater recharge zone. Chitsazan and Akhtari (2009) worked on the similar lines and focused on the GIS based DRASTIC modeling in the Kherran plain of Iran. In association with the conventional modeling, concentration of nitrate in the groundwater was also incorporated and it was observed that southwest and western part of the study area had higher concentration of the elements.…”
Section: Introductionmentioning
confidence: 99%
“…Geographic Information System (GIS) has been proven as an effective tool for this purpose. As in this research, Chitsazan and Akhtari (2009) and Awawdeh and Jaradat (2009) determined the risk of pollutants to contaminate the groundwater, with the help of GIS. In recent years the increase in the popularity of applying environmental criteria in national planning and management has provided a wide range of scientific approaches to determine the best location of hazardous wastes to be land filled (Abessi and Saeedi 2009).…”
Section: Introductionmentioning
confidence: 99%